5th ISCA/DEGA Workshop on Perceptual Quality of Systems (PQS 2016) 2016
DOI: 10.21437/pqs.2016-23
|View full text |Cite
|
Sign up to set email alerts
|

Viva la Resolution: The Perceivable Differences between Image Resolutions for Light Field Displays

Abstract: As 3D display technologies are becoming more and more common in commercial, everyday usage, a special type of 3D known as projection-based light field displays is emerging as well. While holding many key characteristics such as field of view or angular resolution, traditional image resolution also plays a major role in the overall determination of user experience, similarly to 2D displays. The paper investigates the perceivable differences between display resolutions, and presents the acceptability of resoluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 8 publications
0
22
0
Order By: Relevance
“…Suboptimally low spatial resolution manifests in blur that is not uniform across the volume of visualization. While in multimedia use cases, blurred content is often tolerable 18 and can also be visually appealing particularly for computer-generated models and scenes, it may result in false positive or false negative diagnosis in medical imaging. However, at the time of this publication, according to the best knowledge of the authors, no research reports that light-field content above 1920 × 1080 spatial resolution could be efficiently distinguished by viewers, thus capturing and displaying in a resolution higher than that might not be necessary.…”
Section: Discussion On Visualizationmentioning
confidence: 99%
“…Suboptimally low spatial resolution manifests in blur that is not uniform across the volume of visualization. While in multimedia use cases, blurred content is often tolerable 18 and can also be visually appealing particularly for computer-generated models and scenes, it may result in false positive or false negative diagnosis in medical imaging. However, at the time of this publication, according to the best knowledge of the authors, no research reports that light-field content above 1920 × 1080 spatial resolution could be efficiently distinguished by viewers, thus capturing and displaying in a resolution higher than that might not be necessary.…”
Section: Discussion On Visualizationmentioning
confidence: 99%
“…The works of Kara et al address the spatial [17] and angular [18] resolutions, and investigate their interdependence [19]. The authors applied degradations to converted still image contents through reductions in the spatial and angular resolutions, and found that the visual phenomena induced by the disturbed parallax smoothness can be lessened by the blur caused by a low spatial resolution.…”
Section: Resolutionmentioning
confidence: 99%
“…Due to the properties of light field visualization, low content spatial resolution appears differently to the end user; there is no pixelation that is uniform across the entire scene in the plane of the display, instead, the content becomes blurred. We investigated the magnitude of QoE degradation originating from the insufficient content spatial resolution in a paired comparison [17], using a 5-point Degradation Category Rating (DCR) scale [54]. The ratings indicated whether there was any perceivable difference between the resolutions or not, and also the extent of annoyance in case the differences were perceivable.…”
Section: The Concept Of Dynamic Adaptive Streaming Of Light Fielmentioning
confidence: 99%
“…We based our choice of the spatial resolutions on our prior findings in the area [17], and we also aimed at having diversity regarding the differences in perceived quality.…”
Section: A Test Conditions and Video Contentmentioning
confidence: 99%
See 1 more Smart Citation